Pengaruh Retak dan Pelapukan Tanah Terhadap Potensi Kelongsoran Saat Hujan Dengan Uji ERT, IP dan Pemodelan Numerik: The Effect of Cracks and Soil Weathering on Landslide Potential During Rain with ERT, IP and Numerical Modeling Tests - Kumala sari, Putu tantri; Wardani, Mila Kusuma (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2024)
Landslides occurred in the hilly area of ​​Tulakan-Pacitan, East Java. The landslide location is right under the supplies electricity tower to the Java and Bali. The landslide occurred during the rainy season that the intensity reached 1000 mm/month and the maximum was 300 mm/day. Geotechnical observations and geophysical observations, Electrical Resistivity Tomography (ERT) and Induced Polarization (IP) have been carried out. Geotechnical testing stated that the soil conditions in the hilly area around the landslide tended to be good. The results of the ERT and IP tests showed that there were layers weathering and cracks in the landslide area. The weathered and cracked soil conditions were not captured in geotechnical tests. This study was conducted to determine the causes of landslides, in hilly areas with predominantly good soil but experiencing weathering and cracks. Numerical modeling based on limit equilibrium (LEM) and finite element (FEM) was carried out by modeling the presence of soil weathering and cracks. The results of this study indicate that the presence of soil cracks and weathering can reduce slope stability, especially during heavy rain. The number of cracks and the seepage parameter in weathered soil can also affect the stability of a slope, causing landslides.